Modelling regional economic effects of the Öresund link -linking two regional economic models - Anne Kaag Andersen; Christer Anderstig (European Regional Science Association (ERSA), 2001)
The Öresund link, opened in July 2000, is a sixteen-kilometre fixed link with several specific characteristics. E.g., the link connects two countries, Denmark and Sweden and two urban areas, Copenhagen and Malmö, with 1 and 0,5 million people, respectively. Further, the fixed link reaches Denmark nearby Copenhagen Airport, which implies easy access to an international airport for a lot of people in Southern Sweden. No doubt, a fixed link with these features will influence the regional interaction and regional development in many ways. Defining a suitable model approach for assessing the regional economic consequences of the fixed link raises several challenging issues: The problem of dealing with border barriers, the choice between regional and multiregional approaches, the difficulty of modelling short term as well as long term effects. These issues seem too complicated to be dealt with within a single model framework. The paper presents one limited model approach. Two regional economic models, LINE in Denmark and RAPS in Sweden, are linked to each other by a common interaction module, where flows from/to the respective part of the Öresund region are being modelled, with respect to trade, commuting and migration. Preliminary model results are presented, mainly dealing with the impact of building the link.
Keywords: 330